Analysis of Autonomic Modulation in Response to a Session of Aerobic Exercise at Different Intensities in Patients With Moderate and Severe COPD - Leite, Marceli Rocha [UNESP]; Ramos, Ercy Mara Cipulo [UNESP]; Freire, Ana Paula Coelho Figueira [UNESP]; de Alencar Silva, Bruna Spolador [UNESP]; Nicolino, Juliana [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP]; Ramos, Dionei [UNESP] (Taylor & Francis, 2018)
Despite the many benefits of performing physical exercise in patients with chronic obstructive pulmonary disease (COPD), information on the response of acute cardiac autonomic modulation in subjects with moderate and severe COPD during and after an aerobic exercise session at different intensities is unknown. The aim of this study was to evaluate the response of cardiac autonomic modulation in patients with moderate and severe COPD during and after an aerobic exercise session at different intensities. Twenty-seven patients with COPD, divided into: Moderate Group and Severe Group, underwent an aerobic exercise sessions with intensities equivalent to 60% and 90% of velocity corresponding to peak oxygen consumption. The heart rate variability (HRV) indices were analyzed in the time and frequency domains at the following times: at rest, during exercise, immediately after, and 5, 10, and 15 minutes after exercise. In the comparison analysis between the two groups, no differences were observed in any of the HRV indices at different intensities applied. However, it was observed that the exercise caused autonomic changes when the groups were analyzed separately. Sessions of aerobic exercise influence the autonomic modulation in patients with COPD. However, COPD severity did not influence the autonomic nervous system response to exercise and recovery moments; and there was no difference between the exercise intensities.
Keywords: aerobic exercise; Autonomic nervous system; COPD; physical exercise